Blue light-emitting diodes as eco-friendly non-thermal technology in food preservation. (November 2020) - Hyun, Jeong-Eun; Lee, Sun-Young
Abstract: Background: Various food preservation technologies, such as ohmic heating, cold plasma, pulsed electric field, and high-pressure processing, have been investigated as alternatives to conventional technologies in the food industry. Among preservation technologies, light-emitting diodes (LEDs) illumination is widely applied in the agricultural and medical industries for microbial inactivation. Scope and approach: In recent years, interest in LEDs with blue wavelengths and their application in food preservation as an alternative technology to ultraviolet irradiation have increased. Furthermore, several researches have investigated the combined effects of LEDs with blue wavelengths and antimicrobials on inactivating foodborne pathogens. Previous studies have elucidated the antibacterial activity of LEDs with blue wavelengths, but the detailed knowledge of the antibacterial mechanisms is still lacking. Key findings and conclusions: The aim of this review is to provide an overview of current study regarding the antibacterial activity of LEDs with blue wavelengths for the inactivation of pathogenic bacteria in laboratory media and food. This review also examines the antibacterial mechanisms of LEDs on foodborne pathogens. Furthermore, the synergistic effects of combinations of LEDs and other methods of food preservation are outlined. Highlights: LED with blue wavelength could inhibit the growth of various foodborne pathogens. LED with blue wavelength could be used to inhibit pathogens on foods. Bacterial growth inhibition by LED was effective at lower than higher temperatures. LED illumination increases the effectiveness of antimicrobials or photosensitizers. LED induces intracellular ROS and damage cellular components such as DNA.